Model Pembelajaran Pendidikan Agama Islam Dalam Pembinaan Mental Narapidana (Studi Multikasus di Lembaga Pemasyarakatan Kelas I Malang Dan Lembaga Pemasyarakatan Wanita Kelas II-A Malang) - Emqi, Muhammad Fauzy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Replacement of the term â€œprisonâ€ to â€œ Correctional Institute â€œ of course ifÂ you lack good intentions, the administration and guardianship prisonersÂ are not only focused on the good faith judgment alone, but more orientedÂ actions are more humane and adapted to the conditions of prisoners it.Special education functions carried out in prisons, lies in the function toÂ which it aspires, namely the implementation of porses awareness andÂ readjustment of the prisoner (the people who have committed violationsÂ of law, not ordinary people), so they do not violate legal provisions andÂ norms adopted society. Both Correctional Institute has also got ISO9001:2008, for being able to provide good services to the inmates.Â The results showed that: Based on exposure data and discussion of theÂ above results, it can be concluded that: (1) Islamic Educational materialÂ delivered to inmates in Malang Correctional Institute Class I and WomenÂ Correctional Institute Class II-A Malang is about faith (monotheism),and morals, (2) model of Islamic education in mental development ofÂ prisoners conducted in Malang Correctional Institute Class I and WomenÂ Correctional Institute Class II-A Malang is a model of behavior modification.Â (3) mental state inmates after holding the Islamic education learningmodels in Correctional Institute Class I Malang and Women CorrectionalÂ Institute Class II-A Malang.keywords: Learning model, Islamic education learning, Mentaldevelopment